The new approach to the strategic project management in the Polish public administration - Tomasz Janka; Anna Kosieradzka (Foundations of Management, 2019)
The article deals with a way of standardizing project and program management methods in public administration, considering that they have been initiated by a number of administration units having a great autonomy, independently of the government strategy. To manage the government strategy, an original model of the unification process of managing projects and programs executed as part of the strategy and supported by a dedicated IT system has been specially developed and implemented. The essence of the presented approach is to replace the top-down forcing changes toward unifying the project management methodologies used by government administration units by stimulating interest in facilitation and benefits provided by the IT system and, as a result, also a willingness to join the system. Such voluntary joining the system is associated with voluntary adaptation of the previous locally applied management method to the methodology supported by the IT system.
Keywords: H70; 650; government strategy; IT system; project management; project management model; project management office; public administration; public finance; state government